Pension Insurance in Russia: Current state and Transformation Opportunities - D. S. Tulenty; A. S. Ermolaeva; P. G. Raba (Финансы: теория и практика, 2021)
The article examines and analyzes the essence of pension relations in modern Russia. The aim of the article is to study and test the hypothesis that an important factor in ensuring the effectiveness of the Russian pension system is a clear definition of the essence of economic relations in it, as well as adequate legal and organizational formalization of these relations. The scientific novelty of the study lies in the analysis of the validity and adequacy of applying (from terminological to organizational and practical levels) the classical insurance principles in the organization of the pension system, as well as the possibilities of increasing the efficiency of this system on the basis of the insurance sector. The research methodology is based on the analysis of the genesis and current state of the Russian pension system. The results of the study indicate that the structure of the Russian pension system requires serious reorganization, in particular, a clear distinction between the insurance (pension insurance) and non-insurance (pension provision) segments. The authors substantiated that pension insurance should be based on the classical principles of life insurance, and insurers who have an appropriate license obtained under the Law “On the organization of insurance business in the Russian Federation” should be involved in the implementation of this insurance. At the same time, non-state pension funds must either be transformed into life insurers, or acquire new functionality within the framework of pension provision (the non-insurance part of the pension system). The practical implementation of the research results and related recommendations will allow, according to the authors, to organically structure the insurance and non-insurance segments of the Russian pension system and increase its efficiency. The authors conclude that the construction of pension insurance on the basis of the classical principles of life insurance will make it possible to fully use the accumulated global and domestic experience of using life insurance as a reliable instrument for financing pensions. At the same time, it is necessary to extend to pension relations the norms of regulation of the insurance market and state insurance supervision, which have proven their effectiveness.